Nanozymes Regulate Redox Homeostasis in ROS-Related Inflammation - Li, Qing; Liu, Ying; Dai, Xianglin; Jiang, Wei; Zhao, Huan (Frontiers in Chemistry, 2021)
Reactive oxygen species (ROS), in moderate amounts, play an essential role in regulating different physiological functions in organisms. However, increased amounts of ROS may cause oxidative stress and damage to biomolecules, leading to a variety of diseases including inflammation and even cancer. Therefore, ROS scavenging reagents are needed to maintain healthy levels of ROS. With considerable advances in nanotechnology, nanozymes possess SOD or CAT-like activities with outstanding free radical scavenging activity, facile synthesis conditions, and excellent biocompatibility. Based on these extraordinary properties, nanozymes has been used to modulate the redox homeostasis and relieve the ROS-related injury. This has led to the emergence of nanozyme-based therapies. In the current review, we presented recently developed applications of nanozymes to treat ROS-dependent disorders with an emphasis on inflammatory and brain diseases.